2015
DOI: 10.1155/2015/176238
|View full text |Cite
|
Sign up to set email alerts
|

Easterly Wave Disturbances over Northeast Brazil: An Observational Analysis

Abstract: This paper aims to identify the circulation associated with Easterly Wave Disturbances (EWDs) that propagate toward the Eastern Northeast Brazil (ENEB) and their impact on the rainfall over ENEB during 2006 and 2007 rainy seasons (April–July). The EWDs identification and trajectory are analyzed using an automatic tracking technique (TracKH). The EWDs circulation patterns and their main features were obtained using the composite technique. To evaluate the TracKH efficiency, a validation was done by comparing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 44 publications
6
52
0
16
Order By: Relevance
“…When these disturbances propagate toward the eastern NEB they can generate large rainfall amounts specially over the eastern coastal areas (e.g. Gomes et al, 2015;Hounsou-gbo et al, 2015;Kouadio et al, 2012). Rao et al (1993) found that the seasonal variation of the intensity and position of the subtropical high in the South Atlantic Ocean modulates coastal winds during the fall and winter.…”
Section: Factors Influencing Precipitation Regimesmentioning
confidence: 99%
“…When these disturbances propagate toward the eastern NEB they can generate large rainfall amounts specially over the eastern coastal areas (e.g. Gomes et al, 2015;Hounsou-gbo et al, 2015;Kouadio et al, 2012). Rao et al (1993) found that the seasonal variation of the intensity and position of the subtropical high in the South Atlantic Ocean modulates coastal winds during the fall and winter.…”
Section: Factors Influencing Precipitation Regimesmentioning
confidence: 99%
“…Global climate phenomena play an important role over the rainy season variability of ENEB [18,19,30,31]. However, this work has also shown that the periodicity modes of precipitation during the dry season in the ENEB, or more specifically in its central parts, is also affected by large-scale climate factors.…”
Section: Discussionmentioning
confidence: 76%
“…The NEB is exposed to different spatial-temporal rainfall regimes throughout the year. Precipitation at the Northern NEB (NNEB) is characterized by a rainy season from January to May marked by expressive interannual variability [8,16,18,19], and a dry season from June to December characterized by very low amounts of precipitation (near zero). On the other hand, Eastern NEB (ENEB) has the highest annual average precipitation of the NEB, with a wet season from March to August, is also susceptible to annual variations [20,21], but in a different way than the NNEB, while the ENEB dry season might receive substantial amount of precipitation in some years.Many studies have been conducted in order to analyze and characterize such interannual variability of precipitation in NEB, which, however, were predominantly focused on NNEB rainy season [8,10,17,[22][23][24][25][26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Além da localização geográfica e efeitos locais, a distribuição espacial heterogênea da precipitação sobre as mesorregiões no estado do RN pode ser explicada pela atuação de sistemas meteorológicos distintos. Como é o caso por exemplo, da mesorregião Leste, que registram os maiores acumulados anuais, em virtude, principalmente, da atuação com maior frequência e intensidade dos fenômenos da brisa marítima, que carrega umidade do oceano para o interior do continente, favorecendo o aumento dos movimentos convectivos (Teixeira, 2008) e dos Distúrbios Ondulatórios de Leste (DOL), que são oscilações nos campos de pressão e vento, e é o principal sistema meteorológico responsável por provocar chuvas no litoral do NEB entre os meses de Maio a Julho (Torres e Ferreira, 2011;Gomes et al, 2015).…”
Section: Resultsunclassified